Third Hankel Determinant for the Reciprocals of Bounded Turning Functions - Venkateswarlu, B.; Krishna, D. Vamshee; Rani, N.; RamReddy, T. (Eurasian Mathematical Journal, 2017)
The objective of this paper is to introduce a certain new subclass of analytic functions and obtain an upper bound for the third Hankel determinant for the functions belonging to this class, using Toeplitz determinants.